Villafranchian large mammals from the Iberian Peninsula: paleobiogeography, paleoecology and dispersal events - Madurell-Malapeira, J.; Ros-Montoya, S.; Espigares, M.P.; Alba, D.M.; Aurell-Garrido, J.A. (Journal of Iberian Geology, 2014)
The Pleistocene of the Iberian Peninsula is currently a focus of intense paleontological, archaeological and geological research. To a large extent, these inquiries are intended to decipher the ecological factors that might have conditioned early Homo dispersals into the European continent during the late Early Pleistocene. In this respect, the research carried out during the last twenty years in several areas of the Iberian Peninsula (the Guadix-Baza Basin, the Sierra de Atapuerca, the Vallparadís Section and the Banyoles-Besalú Basin) have yielded a large amount of new significant data. Here we review such data and provide for the first time a comprehensive synthesis from a faunal, geological and paleoecological perspectives, by focusing on the relationship between paleoenvironmental conditions and early human dispersals during the late Early Pleistocene in the Iberian Peninsula. In particular, the Iberian fossil record of Early to Late Villafranchian large mammals is synthesized, on the basis of recent publications and unpublished data collected by the authors during the last five years, in order to provide the adequate faunal and paleocological framework for understanding the factors that limited or conditioned human dispersal events.